The beginnings of the Mondragon's cooperative experience - Rafael Altuna (AECOOP Escuela de Estudios Cooperativos, 2014)
This article analyzes the origins and the initial evolution of the Mondragon Cooperative’s Experience (MCE). During these three decades (1955-1985), takes place the emergence and consolidation of the MCE. This Experience, radically innovating in his origin, managed to have 19.161 workers in 1985; sales for value of 841,4 million Euros and a total of 94 cooperatives are associated with Caja Laboral and distributed in the whole Basque geography. In these thirty years, the cooperatives knew economic very favourable conjunctures that they could take advantage to grow, together with more unfavourable periods which opened all the potential of intercooperation to resist and to be stronger. In this period, significant changes took place in the institutional bases of the Group. The deep social, economic and political changes happened in the Basque society, were accompanied by cognitive and normative changes inside the cooperativism, whereas the regulatory aspects were kept. The last one became the most vigorous identity element of the cooperativism.